The Effectiveness of Village Owned Enterprise (BUMdes) Management in Improving Community Welfare in Wedoroklurak Village - Mutrafidah, Rizky Marriery; Sukmana, Hendra (Jurnal Kebijakan Publik, 2025)
This research investigates how effectively Village-Owned Enterprises (BUMDes) management improves the welfare of the community in Wedoroklurak Village. The primary aim of this study is to evaluate how much BUMDes management aids in enhancing the economic and social conditions of the local populace. The research utilizes a qualitative descriptive approach with a case study technique. Information was gathered through detailed interviews with village leaders, BUMDes administrators, and local residents, along with observations and document reviews. The results show that BUMDes management in Wedoroklurak Village has been effectively executed through the creation of productive business ventures, the strengthening of village economic initiatives, and the enhancement of community involvement. BUMDes initiatives have led to job creation, fostered small business development, and produced extra income for the village, which can be used for community improvement. However, there are still several obstacles, such as limited management skills, inadequate program outreach, and challenges in business innovation. Despite these issues, BUMDes remains a crucial local economic entity that aids in enhancing welfare. In summary, the effectiveness of BUMDes management in Wedoroklurak Village is evident in its beneficial impact on community welfare, although more efforts are necessary to improve governance, bolster capacity development, and ensure the sustainability of programs for a more extensive long-term effect.